Intercultural Communication in Multinational Work Environments: A Comparative Analysis of Communication Patterns and Cultural Factors - Gustav Luqman; Fernanda Agathsya (IHSA Institute, 2024)
This study aims to explore intercultural communication patterns in multinational work environments by comparing communication styles across diverse cultural contexts. The research design incorporates a mixed-method approach, combining qualitative interviews and focus groups with quantitative surveys to gather data from employees in multinational corporations. The findings reveal common communication challenges, such as language barriers and cultural differences in communication styles, as well as cultural factors influencing communication preferences. Strategies for effective intercultural communication, including cross-cultural training and technology-mediated communication tools, are identified. Comparative analysis highlights both commonalities and differences in communication patterns across cultures, contributing to a nuanced understanding of intercultural communication dynamics. The study's implications for theory, practice, and future research are discussed, emphasizing the importance of context-specific approaches to intercultural communication in multinational work environments.